Rates of Alexithymia and Its Association With Smartphone Addiction Among a Sample of University Students in Egypt - Elkholy, Hussien; Elhabiby, Mahmoud; Ibrahim, Islam (Frontiers in Psychiatry, 2020)
Introduction Alexithymia is characterized by difficulties in describing feelings. Many studies have shown that there is a relation between alexithymia and different types of addictions. Nowadays, smartphone addiction is proposed to be a global problem. The current study focuses on the rates of alexithymia and its association with smartphone addiction in an Egyptian university. Materials and Methods This is a cross-sectional study that was conducted in Ain Shams University. A sample of 200 university students was surveyed using Toronto Alexithymia Scale (TAS) and Smartphone Addiction Scale–Short Version (SAS-SV). Results The results showed that 44 students (22%) had alexithymia. It was also found that around one third of the sample (N=65, 32.5%) met the criteria of smartphone addiction. There was a strong association between alexithymia and smartphone addiction (OR=4.33, 95% CI 2.15–8.74, p= < 0.001). Conclusion This study supports existing literature indicating the strong association between alexithymia and smartphone addiction.